Autoregulation of MBNL1 function by exon 1 exclusion from MBNL1 transcript - Konieczny, Patryk (Nucleic Acids Res, 2017)
Muscleblind-like proteins (MBNLs) are regulators of RNA metabolism. During tissue differentiation the level of MBNLs increases, while their functional insufficiency plays a crucial role in myotonic dystrophy (DM). Deep sequencing of RNA molecules cross-linked to immunoprecipitated protein particles (CLIP-seq) revealed that MBNL1 binds to MBNL1 exon 1 (e1) encoding both the major part of 5΄UTR and an amino-terminal region of MBNL1 protein. We tested several hypotheses regarding the possible autoregulatory function of MBNL1 binding to its own transcript. Our data indicate that MBNLs induce skipping of e1 from precursor MBNL1 mRNA and that e1 exclusion may impact transcript association with polysomes and translation. Furthermore, e1-deficient protein isoform lacking the first two zinc fingers is highly unstable and its EGFP fusion protein has severely compromised splicing activity. We also show that MBNL1 can be transcribed from three different promoters and that the transcription initiation site determines the mode of e1 regulation. Taken together, we demonstrate that MBNL proteins control steady-state levels of MBNL1 through an interaction with e1 in its precursor mRNA. Insights from our study open a new avenue in therapies against DM based on manipulation of the transcription initiation site and e1 splicing of MBNL1 mRNA.